Emotional Eating: A Virtually Untreated Risk Factor for Outcome Following Bariatric Surgery - Betty E. Chesler (The Scientific World Journal)
Empirical investigations implicate emotional eating (EE) in dysfunctional eating behavior such as uncontrolled overeating and insufficient weight loss following bariatric surgery. They demonstrate that EE may be a conscious or reflexive behavior motivated by multiple negative emotions and/or feelings of distress about loss-of-control eating. EE, however, has not been targeted in pre- or postoperative interventions or examined as an explanatory construct for failed treatment of dysfunctional eating. Three cases suggest that cognitive behavioral treatment (CBT) might alleviate EE. One describes treatment for distress provoked by loss-of-control eating. The first of two others, associated with negative emotions/life situations, link treatment of a super-super-preoperative obese individual’s reflexive EE with 52% excess BMI (body mass index) loss maintained for the past year, 64 months after surgery. The second relates treatment of conscious/reflexive EE with 84.52% excess BMI loss 53 months after surgery. Implications for research and treatment are discussed.